Fatwa debate on porcine derivatives in vaccine from the concept of physical and chemical transformation (Istihalah) in Islamic jurisprudence and science - Rosman, Arieff Salleh; Khan, Aqeel; Ahmad Fadzillah, Nurrulhidayah; Samat @ Darawi, Abdul Basit; Hehsan, Aminuddin; Hassan, Ahmad Muhyuddin; Ghazali, Mohd Al'ikhsan; Haron, Zulkiflee (Innovare Academics Sciences Pvt. Ltd, 2020)
Medical field is one of the key areas in viewing the interconnection between religion and science, both modern and traditional. Religion and science are unanimous in ensuring the good health of humans. However, there are differences in approaches used in interpreting the meaning of 'good' in health care between religion and science, as well as the methods of achieving that objective. Among the issues related to the modern medicine is to which extent that the vaccine used is halal. The use of derivatives from haram sources during vaccine preparation becomes a polemic in the field of Islamic bioethics. There is a clash in methodology when scholars explain the halal status of the modern medicines used, especially those derived from haram substances. Among the concepts that caused the difference in fatwa regarding the use of such medicine is istihalah concept. Differences of previous scholars’ acceptance that are associated to istihalah became the fundemental of fatwa difference in this era. Therefore, this paper will discuss issues in the use of haram substance derivatives in the production of vaccines. Next, istihalah concept is analysed based on opinion from past and present scholars, as well as the correlation of istihalah in vaccines production.